TRADISI RUWATAN: BERSIH BUMI KEARIFAN LOKAL DALAM MITIGASI BENCANA - Hari Lelono (Balai Arkeologi Yogyakarta, 2015)
Tradition worship of ancestral spirits in Tengger occur along with the megalithic culture that is widespread in Indonesia, around 500 BC - 500 AD. Physical culture can be seen the remains of objects such as menhirs, and terraces devoted to the concept of ancestral spirit worship followed by a tradition in the community concerned. Megalithic tradition for a group of tribes, is devoted to the worship of ancestral spirits as ruler of protecting and giving life. Therefore, the purpose of this paper is to determine the Tengger local wisdom in maintaining natural ecosystems by humans, through a tradition that has lasted for generations can overcome the problem of frequent disasters. Efforts are being made in the search for the data to answer these goals, used the method of approach by conducting interviews and observations of one tradition that held that ceremony mayu desa / ruwatan. The ceremony is conducted once a year, but in year five held over the highway at the expense of a buffalo or cow. From the results of these interviews, the data obtained with regard to the meaning, function and purpose of the ceremony mayu desa / ruwatan, related to disaster mitigation issues.